Prognostic impact of the CD34+/CD38− cell burden in patients with acute myeloid leukemia receiving allogeneic stem cell transplantation. Issue 4 (21st February 2017) - Jentzsch, Madlen; Bill, Marius; Nicolet, Deedra; Leiblein, Sabine; Schubert, Karoline; Pless, Martina; Bergmann, Ulrike; Wildenberger, Kathrin; Schuhmann, Luba; Cross, Michael; Pönisch, Wolfram; Franke, Georg‐Nikolaus; et al.
Abstract: In acute myeloid leukemia (AML), leukemia‐initiating cells exist within the CD34+/CD38− cell compartment. They are assumed to be more resistant to chemotherapy, enriched in minimal residual disease cell populations, and responsible for relapse. Here we evaluated clinical and biological associations and the prognostic impact of a high diagnostic CD34+/CD38− cell burden in 169 AML patients receiving an allogeneic stem cell transplantation in complete remission. Here, the therapeutic approach is mainly based on immunological graft‐versus‐leukemia effects. Percentage of bone marrow CD34+/CD38− cell burden at diagnosis was measured using flow cytometry and was highly variable (median 0.5%, range 0%–89% of all mononuclear cells). A high CD34+/CD38− cell burden at diagnosis associated with worse genetic risk and secondary AML. Patients with a high CD34+/CD38− cell burden had shorter relapse‐free and overall survival which may be mediated by residual leukemia‐initiating cells in the CD34+/CD38− cell population, escaping the graft‐versus‐leukemia effect after allogeneic transplantation. Evaluating the CD34+/CD38− cell burden at diagnosis may help to identify patients at high risk of relapse after allogeneic transplantation. Further studies to understand leukemia‐initiating cell biology and develop targeting therapies to improve outcomes of AML patients are needed.